2019
DOI: 10.1186/s12875-019-0917-8
|View full text |Cite
|
Sign up to set email alerts
|

Over prescribing of antibiotics for acute respiratory tract infections; a qualitative study to explore Irish general practitioners’ perspectives

Abstract: Background Anti-microbial resistance (AMR) is a global threat to public health and antibiotics are often unnecessarily prescribed for acute respiratory tract infections (ARTIs) in general practice. We aimed to investigate why general practitioners (GPs) continue to prescribe antibiotics for ARTIs despite increasing knowledge of their poor efficacy and worsening antimicrobial resistance. Methods We used an explorative qualitative study design. Thirteen GPs were recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…These findings are consistent with previous research on perceptions of drivers of outpatient antibiotic prescribing. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] In particular, the perception of patient demand as a driving force behind inappropriate prescribing practices continues to be a consistent finding across studies both in the USA and other countries. Similar perceptions have also been documented among inpatient physicians who believe that prescribers outside of hospitals are primarily responsible for antibiotic overuse and antibiotic resistance, underscoring the value for individual feedback on prescribing patterns to help these physicians recognise the need for antibiotic stewardship in their practice.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These findings are consistent with previous research on perceptions of drivers of outpatient antibiotic prescribing. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] In particular, the perception of patient demand as a driving force behind inappropriate prescribing practices continues to be a consistent finding across studies both in the USA and other countries. Similar perceptions have also been documented among inpatient physicians who believe that prescribers outside of hospitals are primarily responsible for antibiotic overuse and antibiotic resistance, underscoring the value for individual feedback on prescribing patterns to help these physicians recognise the need for antibiotic stewardship in their practice.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies, including those from the USA and Europe, have shown that physicians consider patient demand and prescribing of other physicians to be primary drivers of inappropriate antibiotic prescribing. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] In order to counteract these drivers of inappropriate prescribing, physicians have highlighted a need for improved public education around antibiotic resistance and the need for appropriate prescribing. 20-23 26 Additionally, studies from USA and European countries have shown that physician time constraints, fear of undertreating patients due to diagnostic uncertainty, and certain clinical factors are also seen as drivers of inappropriate prescribing.…”
Section: Introductionmentioning
confidence: 99%
“…Recent qualitative research on this area has explored service users' [32] and prescribers' [33][34][35][36][37] attitudes towards delayed antibiotic prescription, prescribers' attitudes and experiences on antibiotic prescribing [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54], service users' experiences on antibiotic use [38,39,48,51,[55][56][57][58], self-care treatments for ALRTIs [32,59], service users' [48,60] and health professionals' [47,48] understandings of AMR and antibiotic use, interactions between health Committee of the Institut de Recerca en Atenció Primària Jordi Gol i Gurina (IDIAPJGol) (contact via cei@idiapjgol.info) for researchers who meet the criteria for access to confidential data. For more information on data availability restrictions you can contact the ethics committee at cei@idiapjgol.info.…”
Section: Introductionmentioning
confidence: 99%
“…Recent qualitative research on this area has explored service users’ [ 32 ] and prescribers’ [ 33 37 ] attitudes towards delayed antibiotic prescription, prescribers’ attitudes and experiences on antibiotic prescribing [ 38 54 ], service users’ experiences on antibiotic use [ 38 , 39 , 48 , 51 , 55 58 ], self-care treatments for ALRTIs [ 32 , 59 ], service users’ [ 48 , 60 ] and health professionals’ [ 47 , 48 ] understandings of AMR and antibiotic use, interactions between health professionals and service users [ 47 ], experiences of ALRTIs [ 59 ], the role of pharmaceutical companies on antibiotic overprescribing and AMR [ 39 ], and socio-cultural factors to promote adequate antibiotic use [ 61 ]. These studies are mostly focused on health professionals’ experiences (rather than service users’) and take a conventional biomedical perspective to health and AMR.…”
Section: Introductionmentioning
confidence: 99%
“…Today, unfortunately, physicians are able to allocate less than optimal time to the patients for diagnosis because of overcrowded patient to primary healthcare services, and are often under pressure to prescribe antibiotics by patients and/or their relatives (18).…”
Section: Discussionmentioning
confidence: 99%